Contribution to the cockroach genus Ctenoneura Hanitsch, 1925 (Blattodea: Corydioidea: Corydiidae) with descriptions of seven new species from China - Qiu, Lu; Che, Yan-Li; Wang, Zong-Qing (Zootaxa, 2017)
Seven new species of Ctenoneura Hanitsch, 1925, Ctenoneura bawangensis sp. nov., Ctenoneura delicata sp. nov., Ctenoneura elongata sp. nov., Ctenoneura heixuanfeng sp. nov., Ctenoneura helicata sp. nov., Ctenoneura papillaris sp. nov. and Ctenoneura qiuae sp. nov. are described from Hainan and Yunnan, China. Ctenoneura simulans Bey-Bienko, 1969 is redescribed and illustrated. Male genitalia of this genus is described and illustrated for the first time and is found to lack any genital hook. Female Ctenoneura is reported as apterous. Species abundance is estimated. Two species groups are suggested and the taxonomic status of the genus is discussed. A map and a key to males of Chinese Ctenoneura spp. and an updated checklist of the Ctenoneura are provided. Habitat photographs of Ctenoneura are shown for the first time.